Data communications and networking with TCP/IP protocol suite - Forouzan, Behrouz A. (McGraw Hill, 2022)
Data Communications and Networking, 6th Edition, teaches the principles of networking using TCP/IP protocol suite. It employs a bottom-up approach where each layer in the TCP/IP protocol suite is built on the services provided by the layer below. This edition has undergone a major restructuring to reduce the number of chapters and focus on the organization of TCP/IP protocol suite. It concludes with three chapters that explore multimedia, network management, and cryptography/network security. Technologies related to data communications and networking are among the fastest growing in our culture today, and there is no better guide to this rapidly expanding field than Data Communications and Networking.